Creative problem solving method in organizational innovation - Cardoso de Sousa, Fernando (2013)
This research focuses on the development of entrepreneurship projects, using the creative problem solving (CPS) methodology and aims at demonstrating its effectiveness in improving team commitment to entrepreneurship projects. The design follows an adaptation of the 8-step process of Basadur’s problem solving approach (Basadur, 1997), into a 5-step procedure, consisting of fact finding, problem definition, solution finding and action planning. These steps are carried out in two four-hour sessions, using specific techniques that link creative people and management in order to develop a plan of action, thus initiating a system of transformation of the individual and team creativity into organizational innovation. Forty M.A. students, organized in four groups (two in art education and two in tourist entrepreneurship) were submitted to a pre-post test regarding team commitment, prior and after two 4-hour problem solving sessions, following one objective provided by the course director. At the end of the sessions they were also required to fill in a form where they were asked to express their evaluation of the method. Each project designed is now under implementation, and each group is registering all the necessary data to allow for the following up of the project. Results indicated an improvement in individual attitude towards emotional team commitment, during CPS sessions, as well as positive evaluations of the method. The possibilities of making a joint project, using the CPS method, were also demonstrated. Further research is expected once the projects are carried away and more teams involve in the construction of original entrepreneurship projects.